Current knowledge of the implication of lipid mediators in psoriasis - Simard, Mélissa; Morin, Sophie; Ridha, Zainab; Pouliot, Roxane (Frontiers in Immunology, 2022)
The skin is an organ involved in several biological processes essential to the proper functioning of the organism. One of these essential biological functions of the skin is its barrier function, mediated notably by the lipids of the stratum corneum, and which prevents both penetration from external aggression, and transepidermal water loss. Bioactive lipid mediators derived from polyunsaturated fatty acids (PUFAs) constitute a complex bioactive lipid network greatly involved in skin homeostasis. Bioactive lipid mediators derived from n-3 and n-6 PUFAs have well-documented anti- and pro-inflammatory properties and are recognized as playing numerous and complex roles in the behavior of diverse skin diseases, including psoriasis. Psoriasis is an inflammatory autoimmune disease with many comorbidities and is associated with enhanced levels of pro-inflammatory lipid mediators. Studies have shown that a high intake of n-3 PUFAs can influence the development and progression of psoriasis, mainly by reducing the severity and frequency of psoriatic plaques. Herein, we provide an overview of the differential effects of n-3 and n-6 PUFA lipid mediators, including prostanoids, hydroxy-fatty acids, leukotrienes, specialized pro-resolving mediators, N-acylethanolamines, monoacylglycerols and endocannabinoids. This review summarizes current findings on lipid mediators playing a role in the skin and their potential as therapeutic targets for psoriatic patients.